Evaluation of biological characteristics such as age, sexuality and growth parameters of fish roach (Rutilus rutilus caspicus) in the southeastern coasts of the Caspian Sea (Sari and Turkmen of port) - H. Taghavi Jlodar email ; A. Amri Sahebi (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2016)
Purpose of this study was to evaluate the biological parameters of growth and some roach (Rutilus rutilus caspicus) on the southern coast of the Caspian Sea. Therefore, 160 pieces of fish taken from two the regions and some biological characteristics such as age, sexuality and growth, given the importance and development of population and time were studied. The mean (±Standard Deviation) age, body weight and fork length fish roach respectively in Sari and Turkmen of port 2.8±0.68 and 2.4±0.97 years, 18.56±2.12 and 16.5±2.62 cm, 117.67±48.82 and 76.73±36.31 gr. There is a significant correlation between fork length, weight and age of fish (P<0.001). The sex ratio of male to female fish roach in Sari 1:1.5 and Turkmen of port 1.7: 1, which respectively, differences significant are statistically (Sari: t-test=15.39, P<0.001) (Turkmen port: t-test= 18.25, P <0.001). Index GSI (Gonad Somatic Index) in Sari fish roach over the fish roach of Turkmen of port and season gonad growth in both areas was appropriate. The mean condition factor (CF) in Sari and Turkmen of port fish roach showing respectively 1.24±0.14 and 1.12±0.09. Also, the length and weight relationship, positive growth pattern in both locations is displayed. All these factors indicate different status, age, sexuality and growth of the fish is investigated in the two areas.